2001
DOI: 10.4012/dmj.20.24
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NaClO Treatment on Bonding to Root Canal Dentin Using a New Evaluation Method.

Abstract: The purposes of this study were to investigate the reliability and efficiency of a new evaluation method for resin bonding to root canal dentin, which measures both marginal adaptation and shear bond strength simultaneously, and to determine the effects of root canal irrigants on resin bonding. A wet bonding system (Single Bond) and a self-etching primer system (Clearfil Mega Bond) were employed; NaClO was used as a root canal irrigant. No gaps or changes in bond strength were observed despite the NaClO treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
1
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 8 publications
3
31
1
5
Order By: Relevance
“…On the other hand, less-than-ideal resin-dentin adhesion may occur under clinical situations, which may favor the removal of resin-based root canal filling materials. There are several causes that impair resin-dentin adhesion in the root canal system, such as ineffective EDTA conditioning in the deeper part of the canal wall 20) , the use of sodium hypochlorite that may adversely affect bond strength 21,22) , and the presence of uninstrumented areas 23) that may be unfavorable to adhesion. These could explain, at least in part, why it has been reported that Epiphany/Resilon showed lower adhesive strength to dentin 24,25) and was easier to remove compared with gutta-percha and a conventional epoxy resin sealer (AH Plus) [14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, less-than-ideal resin-dentin adhesion may occur under clinical situations, which may favor the removal of resin-based root canal filling materials. There are several causes that impair resin-dentin adhesion in the root canal system, such as ineffective EDTA conditioning in the deeper part of the canal wall 20) , the use of sodium hypochlorite that may adversely affect bond strength 21,22) , and the presence of uninstrumented areas 23) that may be unfavorable to adhesion. These could explain, at least in part, why it has been reported that Epiphany/Resilon showed lower adhesive strength to dentin 24,25) and was easier to remove compared with gutta-percha and a conventional epoxy resin sealer (AH Plus) [14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been many reports on the effects of NaClO application after acid-etching on bond strength to dentin [19][20][21][22][23][24][25][26][27] . On one hand, Prati et al 19) and Saboia et al 20) reported that NaClO treatment removed the unprotected collagen layer after acid-etching and increased the dentin bond strength of some adhesive systems.…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of adhesive systems is directly related to the dentin quality and collagen integrity. The fact that NaOCl is an efficient organic solvent that causes dissolution of dentin collagen fibrils [12,16] might explain its negative influence on the bond strength of the self-adhesive resin cement shown in this study, since collagen plays an important role in the formation of the hybrid layer.…”
Section: Discussionmentioning
confidence: 98%